2014
DOI: 10.1038/ejcn.2014.135
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns derived with multiple methods from food diaries and breast cancer risk in the UK Dietary Cohort Consortium

Abstract: A 'high-alcohol' dietary pattern derived with RRR was associated with an increased breast cancer risk; no evidence of associations of other dietary patterns with breast cancer risk was observed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
1
25
0
3
Order By: Relevance
“…Taken together, 23 additional observational studies (14 cohort studies , and nine case–control studies ) were identified that were not included in the previous meta‐analysis. Two studies were included in the original version of this systematic review, data of these were extracted for the update in a modified form: the cohort by Kenfield et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taken together, 23 additional observational studies (14 cohort studies , and nine case–control studies ) were identified that were not included in the previous meta‐analysis. Two studies were included in the original version of this systematic review, data of these were extracted for the update in a modified form: the cohort by Kenfield et al.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies used the MD score provided by Trichopoulou et al. , 10 studies used the alternate MD score established by Fung et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trois portent sur des populations nordeuropéennes [17][18][19]. Deux portent sur des populations méditerranéennes [20,21] et une étude multicentrique inclut des populations du Nord et du Sud de l'Europe [22].…”
Section: Cancer Colorectalunclassified